Pentingnya Pendidikan Karakter untuk Siswa Sekolah Dasar dalam Semangat Belajar melalui Mencintai Orang Tua di SDN Ambulu 3 - Puspito, Agung Nugroho; Wardhono, Adhitya; Qori’ah, Ciplis Gema; Nasir, M Abd; Suud, Hasbi Mubarak; Fadilah, Iftitah Arya Putri; Lestari, Dhea Suci; Maharany, Adelia Dwifa; Elnadia, Salsabillah Rahmah; Wibowo, Kaisar Belmiro Khalfani; Rahmanda, Rahadian; Prakoso, Bhim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Education is a fundamental component in the development of a nation, particularly for a developing country like Indonesia, which requires a generation of high-quality successors. To support this need, the government has implemented a 12-year compulsory education policy, covering education from Elementary School (SD) to Senior High School (SMA). Elementary School serves as the foundational stage for students' learning. However, academic education alone is insufficient to create a quality generation; character education also plays a key role in shaping individual attitudes. As moral values are increasingly eroded by modern developments, character education becomes even more essential. This study was conducted on 6th-grade students at SDN Ambulu 3, employing an approach that emphasizes the importance of appreciating parents. This approach aims to enhance students' awareness of their parents' roles in their lives and their responsibilities as learners. Data analysis was carried out using a qualitative descriptive method, with letter writing as the research instrument. The results indicate that character education with a focus on appreciating parents is effective in boosting students' enthusiasm for learning.